A preparation method of folding-resistant toughened flame-retardant alloy tile material
By using saturated polyester to coat titanium carbide particles in the daylight tile material, the shortcomings of existing daylight tile materials in terms of fold resistance and toughness are solved, and the fold resistance toughening and flame retardant performance of alloy tile materials are improved.
Patent Information
- Application Number
- CN202310622291.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-05-30
AI Technical Summary
The existing daylight tile materials have shortcomings in terms of fold resistance and toughness, especially the quality of the fiberglass daylight tile is unstable and the overall light transmittance is poor.
Saturated polyester is used to coat titanium carbide particles, and the capacity-enhanced titanium carbide is formed through shear emulsification and ultrasonic dispersion technology, and combined with PET resin, polypropylene resin, flame retardant, etc., and molded through a twin-screw extruder to form a fold-resistant flame-retardant alloy tile material.
It effectively improves the toughness and folding resistance of alloy tile materials, avoids the generation and expansion of microcracks, and improves the light transmittance, weather resistance and processability of the materials, and has many advantages such as corrosion resistance, aging resistance, sound insulation, and heat insulation.
Smart Images

Figure CN116554657B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame-retardant polymer materials, and in particular relates to a method for preparing a folding-resistant, toughened, flame-retardant alloy tile material. Background Art
[0002] Lighting tiles are the key to ensuring the good function of the roof lighting system. First of all, in the direct sunlight environment, the lighting tiles need to have good durability and long service life to reduce maintenance costs. At the same time, in some cases, the lighting tiles also need to resist wind, rain, snow and other bad weather. Therefore, the mechanical properties of the lighting tiles should be better, and the density should not be too large to reduce the pressure on the support and foundation. At the same time, the sunshade itself should have a certain toughness and folding resistance, and it should not break when touched or folded. In the use, transportation, installation, on-site construction, and repair links, the alloy tiles are required to have good toughness, including being able to withstand the impact of strong winds and heavy rains and bending during installation, in order to ensure that the function of the roof lighting system is maximized. At present, the lighting tiles sold on the market include glass lighting tiles, plexiglass, PVC materials, PC translucent panels, FRP fiberglass lighting tiles, etc. PC lighting tiles are haze-free and have good permeability, but they are expensive and have high production costs. Polycarbonate has poor folding resistance, and its durability and scratch resistance are slightly insufficient. In the past, most industrial factory roofs were illuminated by FRP daylighting tiles. To facilitate the connection with the roof, the daylighting tiles are made into the same waveform as the roof panel. At present, most FRP daylighting tiles are handmade, which has some problems: such as unstable quality. Since the production process is to manually apply resin materials on glass felt or cloth, tiny bubbles and cavities that are difficult to distinguish with the naked eye are prone to appear in uneven places to form leaks. FRP daylighting tiles contain glass fibers and have average permeability. Their overall light transmission performance is poor, the haze is large, and the aesthetics is average. For example, 4-5mm high-quality float glass or tempered glass and PC boards are used as daylighting materials for greenhouse covering materials in agriculture. Transparent ABS boards have good processing toughness and colorability, but it is difficult to process ABS boards into curved shapes such as arches, and they have poor compression and flexural properties. Excellent alloy tile materials can be used in the construction of emergency shelters, disaster relief tents, farmers' markets, development zones, residential areas, shopping malls, antique buildings, new rural construction and renovation, awnings, canopies, railway stations, airports, and industrial steel structure factory roofs. CN202011159368.4 A composition and method for preparing a light-transmitting tile resin, which belongs to a fiberglass light-transmitting tile, and does not solve the shortcomings of fiberglass light-transmitting tiles and existing light-transmitting tile materials that are not foldable and have poor toughness. Those skilled in the art are in urgent need of developing a method for preparing a folding-resistant, toughened, and flame-retardant alloy tile material to meet the existing application market and performance requirements. Summary of the invention
[0003] In view of this, the present invention provides a method for preparing a folding-resistant, toughened, and flame-retardant alloy tile material.
[0004] A method for preparing a folding-resistant, toughened, flame-retardant alloy tile material comprises the following steps:
[0005] The first step is to increase the volume and coat the titanium carbide: dissolve the saturated polyester in dichloromethane to obtain a saturated polyester solution with a mass fraction of 10% to 15%, disperse the nano-titanium carbide in a deionized water solution with a mass fraction of 0.01% to 0.05% of fatty alcohol polyoxyethylene ether to form a titanium carbide dispersion with a concentration of 3 to 5 g / L, then add the titanium carbide dispersion to the saturated polyester solution at a volume ratio of 1:2 to 3, shear emulsify to form a saturated polyester emulsion, add a calcium stearate emulsion or a zinc stearate emulsion with a solid content of 15% to 20% to the saturated polyester emulsion under stirring, and use ultrasonic dispersion to assist dispersion, decompress and spin-dry the dichloromethane, centrifuge, rinse and filter the precipitate with clean water, and dry it at 50 to 60°C for 6 to 8 hours to obtain the increased volume and coated titanium carbide;
[0006] Further, the saturated polyester is preferably FILCO470 or FILCO368; for example, FILCO470 is a self-emulsifying saturated polyester resin, and its emulsion film is transparent, soft and sticky, and it has been used as a sizing agent for glass fiber in the past; in the past, calcium stearate emulsion was a coating additive for paper to improve the smoothness and glossiness of paper and prevent calendering powder; zinc stearate emulsion is a building waterproofing agent; in the present invention, calcium stearate emulsion or zinc stearate emulsion is used as an emulsifier component to form a multiple emulsion, which is unstable, and dichloromethane is removed by decompression to obtain a volume-enhanced coated titanium carbide;
[0007] The second step is to mix 65-80 parts of PET resin, 10-20 parts of polypropylene resin, 5-10 parts of compatibilizer, 5-10 parts of flame retardant, 0.15-0.2 parts of anti-aging additive, and 3-5 parts of compatibilizer coated titanium carbide, and melt-extrude to form a composite material. The PET resin, polypropylene resin, compatibilizer, flame retardant, anti-aging additive, and compatibilizer coated titanium carbide are evenly mixed, added into a twin-screw extruder, plasticized, mixed, extruded, and cooled to obtain a folding-resistant, toughened, flame-retardant alloy tile material.
[0008] Furthermore, the temperature of zone 1 of the second-step twin-screw extruder is 195~200°C, the temperature of zone 2 is 200~210°C, the temperature of zone 3 is 210~215°C, the temperature of zone 4 is 235~245°C, the temperature of zone 5 is 245~260°C, the temperature of zone 6 is 250~260°C, the temperature of zone 7 is 250~260°C, the temperature of zone 8 and zone 9 is 250~255°C, and the die head temperature is 260~265°C.
[0009] Furthermore, in the first step of shear emulsification, the rotation speed of the emulsifier is 15000-18000 r / min, and the emulsification time is 5-10 min.
[0010] Furthermore, the first step of ultrasonic temperature is 30-35°C, ultrasonic power is 1000W, ultrasonic frequency is 20kHz, and ultrasonic time is 5-10min.
[0011] Furthermore, the flame retardant in the second step is a mixture of tricresyl phosphate and melamine cyanurate in a ratio of 1:1 to 2 by mass.
[0012] Furthermore, the intrinsic viscosity of the PET resin in the second step is 0.7-0.9 dl / g.
[0013] Furthermore, the compatibilizer in the second step includes one or more of cardanol grafted polypropylene or glycidyl methacrylate grafted polypropylene.
[0014] Furthermore, the anti-aging aid includes one or more of antioxidant 1010, antioxidant 168, and antioxidant 1076.
[0015] Beneficial effects of the present invention:
[0016] The present invention uses saturated polyester to coat titanium carbide particles to form a volume-enhanced coated titanium carbide, which can effectively prevent the generation and expansion of microcracks inside the alloy tile material, play a role in crack pinning, and further have a toughening effect on the alloy tile material. At the same time, the saturated polyester is used for coating, and the titanium carbide is evenly dispersed in the alloy tile material to avoid titanium carbide agglomeration. The saturated polyester and PET can be melt-blended and extruded to make the titanium carbide evenly dispersed in the alloy tile. The chemical coating method is used to coat a layer of saturated polyester on the surface of titanium carbide, which can effectively improve the wettability between titanium carbide and PET. Further, PET / PP is used for blending, and the alloy tile has excellent water resistance, impact resistance and processability. Blending it with PET can promote the crystallization of PET and improve the folding fatigue resistance of PET. The alloy tile has the advantages of corrosion resistance, aging resistance, high light transmittance, beautiful molding, low cost, etc. The alloy tiles produced with weather-resistant flame-retardant polyester as the main raw material have outstanding sound insulation, heat insulation, thermal insulation, low temperature resistance, corrosion resistance, sun resistance, waterproof performance, impermeability, large single sheet area, stable volume, strong fire resistance, impact resistance, insulation, beautiful and light weight, self-cleaning performance, easy installation, and a service life of more than 20 years. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the cross section of the folding-resistant, toughened, flame-retardant alloy tile material. DETAILED DESCRIPTION
[0018] The present invention can be better understood according to the following examples. However, those skilled in the art will readily understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims. Example 1
[0019] Saturated polyester FILCO470, Jiangxi Hongyuan calcium stearate emulsion Quangang Petrochemical cardanol grafted polypropylene, Oak fatty alcohol polyoxyethylene ether AEO2-M, Shouguang Pu'er MCA melamine cyanurate, HS2000, H202, H202A, H203F, American Eastman's PET9921 resin, Sinopec Tianjin polypropylene PPB-M02, Longhua Hanguang Technology 50nm titanium carbide powder, tile thickness 10mm, plate length 6000mm, plate width 1050mm, vertical rib 0.30mm.
[0020] Polypropylene and PET resins are dried before production, the drying temperature is controlled at 120°C, and the moisture content of the dried material should be less than 0.05%.
[0021] The preparation method of the folding-resistant toughened flame-retardant alloy tile material comprises the following steps:
[0022] The first step is to increase the volume and coat titanium carbide: dissolve saturated polyester in dichloromethane to obtain a saturated polyester solution with a mass fraction of 15%, disperse nano-titanium carbide in a deionized water solution with a mass fraction of 0.03% of fatty alcohol polyoxyethylene ether to form a titanium carbide dispersion with a concentration of 4g / L, and then add the titanium carbide dispersion to the saturated polyester solution at a volume ratio of 1:3. The speed of the emulsifier is 16000r / min, the emulsification time is 8min, and shear emulsification is performed to form a saturated polyester emulsion. A calcium stearate emulsion or a zinc stearate emulsion with a solid content of 17% is added to the saturated polyester emulsion under stirring conditions, and ultrasonic dispersion is used to assist dispersion. The ultrasonic temperature is 30°C, the ultrasonic power is 1000W, the ultrasonic frequency is 20kHz, and the ultrasonic time is 8min. After the dichloromethane is dried under reduced pressure, centrifugation is performed, the precipitate is washed and filtered with clean water, and then dried at 50°C for 8h to obtain the increased volume and coated titanium carbide; the second step is to increase the volume and coat titanium carbide by 75% PET resin. 10 parts of polypropylene resin, 7 parts of compatibilizer, 8 parts of flame retardant, 0.18 parts of antioxidant 1010-anti-aging aid, 4 parts of compatibilizer coated titanium carbide, mixed and melt extruded to form a composite material, PET resin, polypropylene resin, compatibilizer, flame retardant, anti-aging aid-antioxidant 1010, and compatibilizer coated titanium carbide are mixed evenly, the flame retardant is a mixture of tricresyl phosphate and melamine cyanurate in a mass ratio of 1:2, the compatibilizer includes cardanol grafted Polypropylene or glycidyl methacrylate grafted polypropylene is added to a twin-screw extruder for plasticization, mixing, extrusion and cooling. The temperature of zone 1 of the twin-screw extruder is 200°C, the temperature of zone 2 is 210°C, the temperature of zone 3 is 215°C, the temperature of zone 4 is 245°C, the temperature of zone 5 is 260°C, the temperature of zone 6 is 260°C, the temperature of zone 7 is 260°C, the temperature of zone 8 is 260°C, the temperature of zone 9 is 255°C, and the temperature of the die head is 265°C to obtain the folding-resistant, toughened and flame-retardant alloy tile material.
[0023] Alloy tile material products: flexibility folded 5 times without breaking at the fold, repeated "flattening and folding" at 25℃ for 50 times without breaking, after 1000h of xenon lamp artificial climate accelerated aging, the tensile strength, elongation at break, and light transmittance remain above 85% of the original, and there is no cracking in cold bending. Example 2
[0024] Saturated polyester FILCO368, Yixing Hujing Chemical HJ14 calcium stearate emulsion, Liaoning Ketong KT-22 methacrylate glycidyl grafted polypropylene, Oak fatty alcohol polyoxyethylene ether AEO9, Taixing MCA cyanuric acid melamine, PET9921 resin, etc., Yanchang Yulin D60P, Longhua Hanguang Technology 50nm titanium carbide powder, tile thickness 10mm, plate length 6000mm, plate width 1050mm, vertical rib 0.30mm.
[0025] Polypropylene and PET resins are dried before production, the drying temperature is controlled at 130°C, and the moisture content of the dried material should be less than 0.05%.
[0026] The preparation method of the folding-resistant toughened flame-retardant alloy tile material comprises the following steps:
[0027] The first step is to increase the volume and coat titanium carbide: dissolve saturated polyester in dichloromethane to obtain a saturated polyester solution with a mass fraction of 10%, disperse nano-titanium carbide in a deionized water solution with a mass fraction of 0.01% of fatty alcohol polyoxyethylene ether to form a titanium carbide dispersion with a concentration of 3g / L, and then add the titanium carbide dispersion to the saturated polyester solution at a volume ratio of 1:3.5. The speed of the emulsifier is 15000r / min, the emulsification time is 10min, and shear emulsification is performed to form a saturated polyester emulsion. A calcium stearate emulsion or a zinc stearate emulsion with a solid content of 15% is added to the saturated polyester emulsion under stirring conditions, and ultrasonic dispersion is used to assist dispersion. The ultrasonic temperature is 30°C, the ultrasonic power is 1000W, the ultrasonic frequency is 20kHz, and the ultrasonic time is 10min. After the dichloromethane is dried under reduced pressure, centrifugation is performed, the precipitate is washed and filtered with clean water, and then dried at 50°C for 6h to obtain the increased volume and coated titanium carbide; the second step is to dissolve the PET resin 65 parts, 10 parts of polypropylene resin, 5 parts of compatibilizer, 5 parts of flame retardant, 0.15 parts of antioxidant 1010-anti-aging aid, 3 parts of compatibilizer coated titanium carbide, mixed and melt extruded to form a composite material, PET resin, polypropylene resin, compatibilizer, flame retardant, anti-aging aid-antioxidant 1010, and compatibilizer coated titanium carbide are mixed evenly, the flame retardant is a mixture of tricresyl phosphate and melamine cyanurate in a mass ratio of 1:1, the compatibilizer includes cardanol grafting The grafted polypropylene or glycidyl methacrylate grafted polypropylene is added into a twin-screw extruder, and the mixture is plasticized, mixed, extruded and cooled. The temperature of the first zone of the twin-screw extruder is 195°C, the temperature of the second zone is 200°C, the temperature of the third zone is 210°C, the temperature of the fourth zone is 235°C, the temperature of the fifth zone is 245°C, the temperature of the sixth zone is 250°C, the temperature of the seventh zone is 250°C, the temperature of the eighth zone is 250°C, the temperature of the ninth zone is 250°C, and the temperature of the die head is 260°C, so as to obtain the folding-resistant, toughened and flame-retardant alloy tile material.
[0028] Alloy tile material products: flexibility folded 5 times without breaking at the fold, repeated "flattening and folding" at 25℃ for 50 times without breaking, after 1000h of xenon lamp artificial climate accelerated aging, the tensile strength, elongation at break, and light transmittance remain above 85% of the original, and there is no cracking in cold bending. Example
[0029] Saturated polyester FILCO368, Dongguan Hanwei zinc stearate emulsion, Quangang Petrochemical cardanol grafted polypropylene, Oak fatty alcohol polyoxyethylene ether AEO2-M, Shouguang Weidong MCA cyanuric acid melamine, PET9921 resin, Sinopec Tianjin polypropylene PPB-M02, Longhua Hanguang Technology 50nm titanium carbide powder, tile thickness 10mm, plate length 6000mm, plate width 1050mm, vertical rib 0.30mm. Polypropylene and PET resins are dried before production, and the drying temperature is controlled at 130°C. The moisture content of the material after drying should be less than 0.05%. The preparation method of folding-resistant toughened flame-retardant alloy tile material includes the following steps:
[0030] The first step is to increase the volume and coat titanium carbide: dissolve saturated polyester in dichloromethane to obtain a saturated polyester solution with a mass fraction of 15%, disperse nano-titanium carbide in a deionized water solution with a mass fraction of 0.013% of fatty alcohol polyoxyethylene ether to form a titanium carbide dispersion with a concentration of 5g / L, and then add the titanium carbide dispersion to the saturated polyester solution at a volume ratio of 1:2. The speed of the emulsifier is 15000r / min, the emulsification time is 10min, and shear emulsification is performed to form a saturated polyester emulsion. A calcium stearate emulsion or a zinc stearate emulsion with a solid content of 20% is added to the saturated polyester emulsion under stirring conditions, and ultrasonic dispersion is used to assist dispersion. The ultrasonic temperature is 30°C, the ultrasonic power is 1000W, the ultrasonic frequency is 20kHz, the ultrasonic time is 5min, and the dichloromethane is dried under reduced pressure and centrifuged. The precipitate is washed and filtered with clean water, and then dried at 50°C for 8h to obtain the increased volume and coated titanium carbide; the second step is to add 80 parts of PET resin, 20 parts of polypropylene resin, and increased volume. 10 parts of agent, 10 parts of flame retardant, 0.2 parts of antioxidant 1010-anti-aging aid, 5 parts of volume-enhancing coated titanium carbide, mixed and melt-extruded to form a composite material, PET resin, polypropylene resin, volume-enhancing agent, flame retardant, anti-aging aid-antioxidant 1010, antioxidant 168, antioxidant 1076 mass ratio of 1:1:1 mixture, volume-enhancing coated titanium carbide are mixed evenly, the flame retardant is a mixture of tricresyl phosphate and melamine cyanurate in a mass ratio of 1:1, the volume-enhancing coated titanium carbide is mixed evenly, the flame retardant is a mixture of tricresyl phosphate and melamine cyanurate in a mass ratio of 1:1, the volume-enhancing agent is The invention comprises cardanol grafted polypropylene or glycidyl methacrylate grafted polypropylene, which are added into a twin-screw extruder for plasticizing, mixing, extruding and cooling. The temperature of the first zone of the twin-screw extruder is 200°C, the temperature of the second zone is 205°C, the temperature of the third zone is 213°C, the temperature of the fourth zone is 240°C, the temperature of the fifth zone is 250°C, the temperature of the sixth zone is 255°C, the temperature of the seventh zone is 255°C, the temperature of the eighth zone is 250°C, the temperature of the ninth zone is 253°C, and the temperature of the die head is 263°C, so as to obtain the folding-resistant, toughened and flame-retardant alloy tile material.
[0031] Alloy tile material products: flexibility folded 5 times without breaking at the fold, repeated "flattening and folding" at 25℃ for 50 times without breaking, after 1000h of xenon lamp artificial climate accelerated aging, the tensile strength, elongation at break, and light transmittance remain above 85% of the original, and there is no cracking in cold bending.
[0032] The performance of the folding-resistant toughened flame-retardant alloy tile materials obtained in Examples 1 to 3 was tested. The test results are shown in Table 1
[0033] Table 1 Performance test results of folding-resistant toughened flame-retardant alloy tile materials obtained in Examples 1 to 3
[0034]
[0035] Note: The standard environment for sample state adjustment and testing is carried out under the environmental conditions specified in GB / T2918-2018 for 6 hours; the cold bending performance test is carried out under the ambient temperature of -20℃, and the alloy tile material is cold bent along the rib direction on a gauge with a radius of 175 times the thickness of the alloy tile to observe whether there are cracks. Tensile strength determination The determination of tensile yield strength is carried out in accordance with the provisions of GB / T1040.2-2022, 250mm / min1A type. Bending strength determination The determination of bending strength is carried out in accordance with the provisions of GB / T9341-2008; Shore hardness determination The determination of Shore hardness is carried out in accordance with the provisions of GB / T2411-2008; Heat deformation temperature determination The determination of heat deformation temperature is carried out in accordance with the provisions of GB / T1634.1-2019, 1.81MPa. Linear expansion coefficient determination The determination of linear expansion coefficient is carried out in accordance with the provisions of GB / T1036-2008. Drop hammer impact test The drop hammer impact test is carried out in accordance with the provisions of GB / T14153-1993, with a 2kg steel ball at a distance of 2m. Combustion performance determination The combustion performance determination is carried out in accordance with the provisions of GB / T8624-2012. Determination of heat transfer coefficient The heat transfer coefficient is carried out in accordance with the provisions of GB / T8484-2020. Determination of light transmittance The light transmittance is carried out in accordance with the provisions of GB / T2410-2008.
Claims
1. A method for preparing a folding-resistant, toughened, flame-retardant alloy tile material, characterized in that: The following steps are involved: The first step is to increase the volume and coat the titanium carbide: dissolve the saturated polyester in dichloromethane to obtain a saturated polyester solution with a mass fraction of 10% to 15%, disperse the nano-titanium carbide in a deionized water solution with a mass fraction of 0.01% to 0.05% of fatty alcohol polyoxyethylene ether to form a titanium carbide dispersion with a concentration of 3 to 5 g / L, then add the titanium carbide dispersion to the saturated polyester solution at a volume ratio of 1:2 to 3, shear emulsify to form a saturated polyester emulsion, add a calcium stearate emulsion or a zinc stearate emulsion with a solid content of 15% to 20% to the saturated polyester emulsion under stirring conditions and disperse with the aid of ultrasonic dispersion, add it to the saturated polyester emulsion for 5 to 10 minutes, reduce the pressure and spin dry the dichloromethane, centrifuge, rinse the precipitate with clean water, filter it, and dry it at 50 to 60°C for 6 to 8 hours. , that is, to obtain the expanded and coated titanium carbide; the second step, 65-80 parts of PET resin, 10-20 parts of polypropylene resin, 5-10 parts of compatibilizer, 5-10 parts of flame retardant, 0.15-0.2 parts of anti-aging additive, and 3-5 parts of expanded and coated titanium carbide are mixed and melt-extruded to form a composite material: PET resin, polypropylene resin, compatibilizer, flame retardant, anti-aging additive, and expanded and coated titanium carbide are evenly mixed, added into a twin-screw extruder, plasticized, mixed, extruded, and cooled to obtain a folding-resistant, toughened, flame-retardant alloy tile material, wherein the flame retardant is a mixture of tricresyl phosphate and melamine cyanurate in a mass ratio of 1:1~2; the compatibilizer includes one or more of cardanol grafted polypropylene or glycidyl methacrylate grafted polypropylene.
2. The method for preparing the folding-resistant toughened flame-retardant alloy tile material according to claim 1, characterized in that: The temperature of zone 1 of the second-step twin-screw extruder is 195~200°C, the temperature of zone 2 is 200~210°C, the temperature of zone 3 is 210~215°C, the temperature of zone 4 is 235~245°C, the temperature of zone 5 is 245~260°C, the temperature of zone 6 is 250~260°C, the temperature of zone 7 is 250~260°C, the temperature of zone 8 and zone 9 is 250~255°C, and the die head temperature is 260~265°C.
3. The method for preparing the folding-resistant toughened flame-retardant alloy tile material according to claim 1, characterized in that: In the first step of shear emulsification, the rotation speed of the emulsifier is 15000-18000 r / min, and the emulsification time is 5-10 min.
4. The method for preparing the folding-resistant toughened flame-retardant alloy tile material according to claim 1, characterized in that: The first step of ultrasonic temperature is 30-35°C, ultrasonic power is 1000W, ultrasonic frequency is 20kHz, and ultrasonic time is 5-10min.
5. The method for preparing the folding-resistant toughened flame-retardant alloy tile material according to claim 1, characterized in that: The intrinsic viscosity of the PET resin in the second step is 0.7-0.9 dl / g.
6. The method for preparing the folding-resistant toughened flame-retardant alloy tile material according to claim 1, characterized in that: The anti-aging aid includes one or more of antioxidant 1010, antioxidant 168, and antioxidant 1076.
Citation Information
Patent Citations
Composition and method for preparing lighting tile resin
CN112251006A
Halogen-free stibium-free antiflaming polydiethylene terephthalate engineering plastics and method for preparing same
CN101768338A
Production technology of glass fiber nanometer enhanced APET (amorphous polyethylene terephthalate) corrugated tile
CN105907050A
Method for producing resin particle, resin composition therefor and resin particle
JP2006328218A
Thermoplastic resin-based molding composition
US4891399A